Avaliação da correlação entre o trabalho essencial de fratura (EWF) e o grau de gelificação de compostos de PVC rígido - Laurini, Rafael Vilela (2011)
Poly(vinyl chloride) or PVC is among the most consumed thermoplastics in the world and has great versatility: A wide range of products, from pipes and rigid window frames to flexible foams, various types of materials such as synthetic leather clothing and flexible sheet can be made from PVC. The mechanical performance of the final product of PVC has direct relationship with the severity of the processing conditions, which can be quantified by the gelation level. This work studied the correlation between the gelation level of rigid PVC samples and the specific essential work of fracture (we), obtained by techniques of analysis of the essential work of fracture (EWF). For this assessment, and in order to control the gelation level, PVC compounds were processed in a torque rheometer, and then molded by compression. Different processing temperatures and two dosage levels in the mixture chamber were used to obtain samples with gelation levels between 2% and 74%, assessed by differential scanning calorimetry (DSC). EWF results showed that in PVC samples with low gelation level occur predominantly brittle fracture, while the progressively increasing of gelation level leads to an increasing of ductile portion in the fracture mechanism of the samples. However, samples with excessively high or excessively low gelation levels showed lower we values, when compared to samples with intermediate gelation levels, supported by both industry experiences and results from other researchers, when other techniques were used.